WOLFIT APPS : PLATFORM DIGITAL INOVATIF UNTUK MENGATASI IMPLIKASI FOODWASTE DARI INDUSTRI FOOD AND BEVERAGE HOTEL DAN RESTORAN - Ani Setiowati; Awin Mulyati (Cahaya Ilmu Bangsa, 2025)
Food waste is a significant issue in the food and beverage (F&B) industry, particularly in the hotel and restaurant sectors, which not only result in financial losses but also have a negative impact on the environment. Every year, the F&B industry contributes significantly to the global food waste figures, which amount to 1.3 billion tons. To address this problem, the author and the team of students from the Program Mahasiswa Wirausaha (PMW) 2024 at the University of 17 Agustus Surabaya developed WOLFIT APPS, a digital platform designed to help manage inventory, predict food demand, and optimize food waste management. WOLFIT APPS utilizes advanced technology to reduce raw material waste and minimize its environmental impact. This application focuses not only on operational efficiency but also on more responsible food waste management, allowing F&B business managers to recycle or donate leftover food. With WOLFIT APPS, it is expected that the F&B industry will transition to a more sustainable and environmentally friendly model while also providing positive impacts to society.